The Fourth Data Release of the Sloan Digital Sky Survey - al., J.K. Adelman-McCarthy et; Gray, Jim; al., et. (Astrophysics, 2006)
This paper describes the fourth data release of the Sloan Digital Sky Survey (SDSS), including all survey-quality data taken through June 2004. The data release includes five-band photometric data for 180 million objects selected over 6670 deg^2, and 673,280 spectra of galaxies, quasars, and stars selected from 4783 deg^2 of that imaging data using the standard SDSS target selection algorithms. These numbers represent a roughly 25% increment over those of the Third Data Release. The Fourth Data Release also includes an additional 131,840 spectra of objects selected using a variety of alternative algorithms, to address scientific issues ranging from the kinematics of stars in the Milky Way thick disk to populations of faint galaxies and quasars.